Carved in stone - Ana Catarina Basílio (Documenta Praehistorica)
The late 3rd millennium BC petrification phenomenon in southern Portugal challenges traditional interpretations, and invites us to explore the complex interplay between prehistoric memory and identity. Found at key mnemonic sites, like the ditched enclosures of Perdigões, Santa Vitória, and Bela Vista 5, these non-funerary stone agglomerations – comprising recutting infillings and a cairn – extended beyond mere functionality. They likely embodied powerful symbols, either by preserving cultural traditions amidst societal transformations or by deliberately and socially erasing past identities. Ultimately, this study examines these agglomerations as ideological tools that reshaped collective memory during the transition between the Chalcolithic and Bronze Age, shedding light on the more intangible behaviours of past communities.